PENGARUH SUPLEMENTASI SENG DAN ZAT BESI TERHADAP TINGKAT KECUKUPAN ENERGI BALITA USIA 3 – 5 TAHUN DI KOTA SEMARANG - Maharani, Dara Gumintang; Kusumastuti, Aryu Candra (Journal of Nutrition College, 2017)
Background: Nutritional intake associated with appetite and eating habits infant. Low appetite in infant would affected low energy intake. Not only energy intake, but also the intake of micronutrients, especially zinc and iron. Lack of energy in the long term can reduce the nutritional status of children. Based Riskesdas 2013, the prevalence of malnutrition and malnutrition increased from 2007 to 2013. Malnutrition in 2013 reached 5.7%, while for 13.9% of malnutrition.Methods: This was quasi experimental with a randomized control group pre-post test design. Subjects were children aged 3-5 years in Semarang as many as 36 subjects and divided into 4 groups (9 subjects/group) with random sampling consisting of one control group who were given placebo and 3 treatment groups. Each of the treatment group was supplemented with zinc, iron, and zinc-iron for 60 days. Dosage of zinc and iron was 10 mg/day and 7,5 mg/day. Food intake obtained by the method of Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Analysis of data using Paired T-Test and Kruskal-Wallis testResults: For 36 infants subyek divided into 20 boys and 16 girls infant. Most of the Infant energy adequacy levels classified on adequate category (75%). After given intervention which group1,2 and 3 not had a significant effect on energy adequacy levels. There only had effect on group 4 toward energy adequacy levels.Conclusion: Zinc and iron supplementation had effect increased energy adequacy levels on infant 3-5 years old.